Analisis Hukum Perlindungan Anak di Indonesia terhadap Eksploitasi Anak oleh Orang Tua dalam Praktik Mengemis - Abdul Haris Nasution; Zulfahmi Zulfahmi; Asrofi Asrofi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Child exploitation in Indonesia, especially by parents in the practice of begging, is a serious problem that violates children's human rights. This research analyzes law enforcement against criminal acts of child exploitation based on Law No. 23/2002 on Child Protection, which prohibits economic exploitation and provides strict sanctions. Despite the legal provisions, implementation and law enforcement still face significant challenges, including economic factors, low parental education, and social norms that consider begging as normal. This research uses a normative juridical method with a statutory and case approach to evaluate the application of the law and provide recommendations. The results show that the lack of legal awareness and rehabilitation support for victims hinders the effectiveness of protection. Therefore, collaboration between the government, law enforcement officials, and the community is needed to raise awareness about children's rights, strengthen law enforcement, and provide sustainable social interventions. With concrete steps, it is hoped that the protection of children from exploitation can be effectively realized.